On looking [compact disc, unabridged] : eleven walks with expert eyes - Horowitz, Alexandra (Simon & Schuster Audio, 2013)
On Looking begins with inattention. It is about attending to the joys of the unattended, the perceived 'ordinary.' Horowitz encourages us to rediscover the extraordinary things that we are missing in our ordinary activities. Even when engaged in the simplest of activities like taking a walk around the block, we pay so little attention to most of what is right before us that we are sleepwalkers in our own lives.